Key Thinkers in Critical Communication Scholarship
XX, 252 p.
Keywords: The personal anecdotes and candid reflections on the lives and work of these important critical scholars, and their predictions on the future of the field, make this book a valuable resource for scholars and students of communication, media studies, political economy, political science, and those interested in critical theoretical approaches.